2020
DOI: 10.47102/annals-acadmedsg.2019198
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Transcatheter Aortic Valve Implantation in Intermediate and Low Risk Severe Aortic Stenosis Patients in Singapore

Abstract: Introduction: Singapore has the world’s second most efficient healthcare system while costing less than 5% GDP. It remains unclear whether transcatheter aortic valve implantation (TAVI) is cost-effective for treating intermediate-low risk severe aortic stenosis (AS) patients in a highly efficient healthcare system. Materials and Methods: A two-phase economic model combining decision tree and Markov model was developed to assess the costs, effectiveness, and the incremental cost-effectiveness ratio (ICER) of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 33 publications
(37 reference statements)
0
35
1
Order By: Relevance
“…In addition to those identified in the systematic reviews, 8 relevant economic evaluations 22,24,[27][28][29][30][31][32] were identified. All 8 economic evaluations 22,24,[27][28][29][30][31][32] were conducted as cost-utility analyses and incorporated Markov models that included between 2 31 and 9 24,28,29 health states. The time horizons were 8 years, 32 15 years, 24,[27][28][29] and lifetime.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to those identified in the systematic reviews, 8 relevant economic evaluations 22,24,[27][28][29][30][31][32] were identified. All 8 economic evaluations 22,24,[27][28][29][30][31][32] were conducted as cost-utility analyses and incorporated Markov models that included between 2 31 and 9 24,28,29 health states. The time horizons were 8 years, 32 15 years, 24,[27][28][29] and lifetime.…”
Section: Methodsmentioning
confidence: 99%
“…All 8 economic evaluations 22,24,[27][28][29][30][31][32] were conducted as cost-utility analyses and incorporated Markov models that included between 2 31 and 9 24,28,29 health states. The time horizons were 8 years, 32 15 years, 24,[27][28][29] and lifetime. 22,30,31 The analysis by Himmels 31 used a decision tree model for the initial 2 years of analysis that fed into a Markov model with 1-year cycles with 2 states: alive and dead.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations